Nurses' and patients' experiences of family planning services in a rural district, South Africa - Kartik Naidoo; Louis S. Jenkins (AOSIS, 2023)
Background: Family planning (FP) is a key component of primary health care (PHC). Nurses are the first source of FP information to women outside their social context. There is a paucity of research regarding clients' lived experiences of FP, particularly understanding both the client's and the healthcare worker's experiences in the same clinical context and community. Aim: This study aims to explore the lived experiences of nurses and female clients regarding FP services at PHC clinics. Setting: Two PHC clinics in a rural sub-district in South Africa. Methods: A descriptive qualitative study using semi-structured interviews was conducted. Clients and nurses were selected using criterion-based purposive sampling and interviewed by female research assistants in a home language in a private setting. Transcription and translation of audio recordings were done. Data were analysed inductively using the framework method. Results: Ten clients and eight nurses were interviewed, with an equal number from each clinic. The median age of clients was 28.5 years and of nurses was 47.5 years. Four themes emerged: (1) Stigma, culture and the teenage girl; (2) Bad effects - the Big Five, clustered around weight changes, blood blockages and abnormal bleeding, pain, fertility and cancer; (3) FP social dynamics; and (4) FP and the health system. Conclusion: Family planning is highly moralised and stigmatised. Negative effects of FP were not adequately recognised by the health system. Family planning outreach into the community and dedicated FP resources at clinics were suggestions to improve the service. Contribution: This work helps to better understand patients' experiences of family planning services.